The Term Son of God as a Proof of Jesus' Humanity: A Biblical Analysis - Zaifuddin Md Rasip (Faculty of Islamic Development Management Universiti Islam Sultan Sharif Ali, 2023)
Trinity is the most important doctrine in Christianity. The concept of the Trinity has made Jesus divine. One of the arguments that is often used as proof of Jesus' divinity is that the term "Son of God" as it is found in the Bible. The focus of this paper is to examine the term “Son of God” as stated in the Holy Bible as a proof of Jesus' divinity or in fact it is a proof of his humanity. The main objective of this research is to discover the meaning of the term Son of God in the context of the Old Testament and New Testament. The research also examines the verses in the Bible which confirm the humanity of Jesus. Since the paper discuses fundamental doctrines in Christianity, the method of the study involves extensive textual analysis. The result of the study shows that the term “Son of God” cannot be understood in the literal sense, rather in its metaphorical sense.